2022
DOI: 10.3389/fonc.2022.816198
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of camrelizumab plus transarterial chemoembolization in intermediate to advanced hepatocellular carcinoma patients: A prospective, multi-center, real-world study

Abstract: ObjectiveCamrelizumab is a newly developed program-death receptor one inhibitor; the real-world evidence about its application in hepatocellular carcinoma (HCC) treatment is lacking. Therefore, this prospective, multi-center, real-world study evaluated the efficacy and safety of camrelizumab plus transarterial chemoembolization (TACE) in treating intermediate-to-advanced HCC patients.MethodsThis study consecutively enrolled 101 intermediate to advanced HCC patients. All patients received camrelizumab-based tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…The systemic agent-attributed AEs observed in this study were relatively common in previous studies ( 26 , 27 ), and no grade 4 AEs or treatment-related death occurred in the two groups. The most common AEs that occurred in this study included hypertension, skin rash, proteinuria, and reactive cutaneous capillary endothelial proliferation (RCCEP), which were also similar to those in previous research.…”
Section: Discussionsupporting
confidence: 62%
“…The systemic agent-attributed AEs observed in this study were relatively common in previous studies ( 26 , 27 ), and no grade 4 AEs or treatment-related death occurred in the two groups. The most common AEs that occurred in this study included hypertension, skin rash, proteinuria, and reactive cutaneous capillary endothelial proliferation (RCCEP), which were also similar to those in previous research.…”
Section: Discussionsupporting
confidence: 62%
“…The combination interestingly provided higher response rates even outside the ablated zone supporting the notion that systemic treatment may augment locoregional strategies and vice versa. Further studies built on this premise and demonstrated that TACE + anti-PD1 may provide a survival benefit to either standalone treatment in intermediate and advanced stage, respectively (56,57). Similar results have been reported for transarterial radioembolization (TARE) which was able to elicit a response rate of 30.6% when combined with nivolumab compared to 20% as monotherapy (58).…”
Section: Enhancing the Efficacy Of Intraarterial Therapies In Interme...supporting
confidence: 57%
“…Besides, Guo et al found that 75% of patients in the TACE plus camrelizumab group had at least one AE associated with camrelizumab, and no patient developed serious AE [ 35 ]. The total incidence of AE in a prospective study with TACE and camrelizumab was 90.1%, and most of them were grade 1–3 [ 36 ]. In our study, the rates of immunotherapy-related AE (such as RCCEP) were also comparable to those seen in the Ju study's AC or TACE + AC cohort.…”
Section: Discussionmentioning
confidence: 99%